Malawian Women In Agriculture Post Cyclone Freddy - Thierfelder, Christian L.; Nkosi, Phindiwe (CGIAR System Organization, 2023)
This blog post is about how the female farmers of Malawi are coping with the after effects of the cyclone Freddy. The blog is based on information gathered during the first virtual field tour that took place on 4 April 2023.